Food sovereignty in sub-Saharan Africa: Reality, relevance, and practicality - Mudombi-Rusinamhodzi, Grace; Rusinamhodzi, Leonard (Frontiers in Agronomy, 2022)
The recent discourse on food sovereignty places much emphasis on democracy in determining localized food systems, and whether the food is culturally appropriate while leaning heavily on sustainable agricultural practices such as organic agriculture, ecological intensification, agroecology, nature-based solutions, and regenerative agriculture. The sustainable agricultural practices are intended to ensure that the land is managed without the use of synthetic fertilizers and pesticides, while going further by focusing on improvements on soil and land health. However, what are the practicalities of food activism and relying entirely on nature while yields are still very low in much of sub-Saharan Africa (SSA)? We attempt to answer this question in four main sections: (a) we start by defining the concept of food sovereignty and the associated practices, (b) we highlight some of the main socio-ecological conditions that are common in SSA, and (c) we present evidence of some of the limitations of food sovereignty due to the diversity in ecological, political, cultural and socio-economic contexts that characterize SSA, (d) finally we focus on food preferences, marketing and certification aspects. We conclude that agroecology alone cannot solve the multiple objectives of increasing crop productivity and replenishing soil nutrients especially on small farms and relying on natural rainfall. There is urgent need to combine superior crop varieties and judicious use of external inputs in tandem with manipulation of the agroecological processes to increase efficiency of input use, achieve higher food productivity, resilience to climate change and preservation of the natural resource base in specific locations.